Attenuation of quorum sensing using computationally designed polymers - Stavroulakis, Georgios (Cranfield University, 2010)
It is generally accepted that the majority of Gram-negative and Gram-positive bacteria communicate via production and sensing of small signal molecules, autoinducers. The ability of bacteria to sense their population density is termed quorum sensing (QS). Quorum sensing controls certain phenotypic traits, particularly virulence factors and biofilm formation. In this project a new solution for the attenuation of quorum sensing which involves selective sequestering of the signal molecules using rationally designed synthetic polymers was explored. Cont/d.